ANALISIS EFEKTIVITAS BIAYA TERAPI GAGAL JANTUNG KONGESTIF PADA PASIEN RAWAT INAP DI RSUD MUARA TEWEH PERIODE JULI-NOVEMBER 2021 - Dedi Hartanto; Anida Anida; Retna Eka Dewi (Akademi Farmasi Yarsi Pontianak, 2022)
Cost-Effectiveness Analysis (CEA) is a method in pharmacoeconomics used to analyze a therapy that is clinical and cost. The purpose of this study was to determine the direct medical costs and to find out which cost-effective therapy for patients with Congestive Heart Failure (CHF) was used in RSUD Muara Teweh for the period July-November 2021. This study was an analytical observational study by taking secondary data. Retrospectively from medical records, details of financial costs, and details of medical costs. The data collection technique used is a total sampling technique. There are 26 people who meet the inclusion criteria and exclusion criteria from a total population of 42 people. The data from this study were grouped based on the class of CHF drug therapy. The results of this study showed that the Diuretic groups were the most effective therapy in reducing blood pressure in CHF patients with effectiveness value of 0,58. The most cost-effective drug class based on the ACER value is ACE-I with the smallest ACER value of Rp. 3.670.770.